Charged Dislocation in Ice. I. Existence and Charge Density Measurement by X-Ray Topography - Itagaki,Kazuhiko (1979)
The motion of dislocations in single crystal ice under an electric field was observed by using X-ray topographic methods. Electric charge density on these dislocations was deduced from the amplitude and length of the dislocation segment under the known AC electrical field. The most likely linear charge density was about +5 x 10 to the minus 11th power c/m, although considerable variation is possible depending on the effective field acting on the dislocation lines. (Author)